The development of an arousal and anxiety control mental skills training programme for the Rhodes University archery club - Chiweshe, Malvern Tatenda (Rhodes University, Faculty of Humanities, Department of Psychology, 2013)
Research on the development of Mental Skills Training (MST) programmes in sport psychology has largely increased as sport has become more competitive. MST programmes have been seen to improve the performance of athletes. This particular research study focuses on the development of an anxiety and arousal control MST programme designed specifically for, and tailored exclusively to, the needs of four archers from the Rhodes Archery Club in Grahamstown, Eastern Cape, South Africa. The development of the programme was guided by the Organisational Development Process model as the research methodology design. Data from two quantitative measures (CSAI-2 and Sport Grid-R), a focus group, and an individual interview were integrated with currently existing mental skills literature and theory to devise this particular MST programme. The results of the assessment phase showed that individual archers have different experiences in how anxiety and arousal affect their performances. The results also showed that archers have different zones in which they feel their performance is good. These zones depend on their subjective interpretations of anxiety and arousal. The results also showed that other factors that include personality differences, level of experience and level of expertise also influence how anxiety and arousal affect performance. The archers had previous exposure to MST programmes although they had not received systematic training in mental skills training. The programme was developed in the form of MST workshops that would run over a three week period. As part of the programme the archers would be given a mental skills manual to aid in the mental skills training. It is recommended in future that more research in MST programmes be done as a way of improving the performance of athletes in South Africa
Keywords: Anxiety; Arousal; Mental skills; Training; Sports -- Psychological aspects -- Research -- South Africa; Archers -- Training of -- Research -- South Africa; Archers -- Psychological aspects -- Research -- South Africa; Psychology, Applied